Peran Koperasi “Agar Makmur Sentosa” dalam Pengembangan Usaha Budidaya Rumput Laut di Dusun Tlocor, Desa Kedungpandan, Kec. Jabon, Kab. Sidoarjo - Sabrina Ade Ulina Saragih; Ananta Prathama (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The limitations in the development of seaweed cultivation business require development with the involvement of the government, seaweed associations, private sector cooperation and through business entities in the form of cooperatives. The Agar Makmur Sentosa Cooperative was formed because of the awareness that seaweed farmers in Tlocor were not yet fully prosperous even though there was great potential for seaweed cultivation as an export commodity. The purpose of this study was to describe the role of the "Agar Makmur Sentosa" Cooperative in the development of seaweed cultivation business in Tlocor Hamlet, Sidoarjo Regency. The research method used was descriptive qualitative which was analyzed using the theory of the role of the public sector according to Jones in Mahsun (2006), namely Regulatory Role, Enabling Role, Direct Provision of Goods and Services. The results of the study stated that the Agar Makmur Sentosa Cooperative had carried out its role in the development of seaweed cultivation business quite well, namely in the Regulatory Role the cooperative had carried out it well in accordance with the regulations in the Cooperative's AD/ART and the Law related to Cooperatives, namely covering the marketing service procurement program, implementation of the RAT. In the Enabling Role indicator, it has been implemented quite well, but in the coaching program for farmer groups, evaluation is needed. In the Direct Provision of Goods and Services indicator, supervision has been carried out well as evidenced by the implementation of seaweed purchasing management and the implementation of evaluation.